Flora of lichens, mosses and liverworts of Wrangel Island: New records - Evdokimov, Gregory; Afonina, Olga; Konoreva, Liudmila; Obabko, Roman; Mamontov, Yuriy; Chesnokov, Sergey; Frolov, Ivan V.; Babiy, Ulyana V. (Polish Polar Research, 2022)
New records to lichen flora and bryoflora of Wrangel Island are presented. The additions to the island cryptogam flora include 32 lichens and one lichenicolous fungus, 26 mosses and eleven liverwort species. Acarospora sinopica, Alectoria gowardii, Austroplaca sibirica, Calogaya bryochrysion, Hymenelia ceracea, Porpidia ochrolemma, and Sagiolechia protuberans are new to the island and to the Russian Far East. Two lichen species (Lecidea lithophila and Rinodina terrestris), as well as two liverwort taxa (Clevea hyalina, Lophoziopsis excisa var. elegans and Pseudolophozia debiliformis), are new to the Chukotka Autonomous Area. Two of the reported moss species (Funaria arctica and Schistidium umbrosum) are extremely rare. Location data and ecological descriptions for the newly reported species are included.